Study on Nonlinear Response of Liquefiable Soils Based on 1G Shaking Table Tests Induced by Spectrum-Compatible Bi-directional Accelerograms - Asami, Kento; Kaho, Ryota; Inoue, Kazuma; Ueda, Kyohei; Hattori, Takao; Serikawa, Yuko (Japanese Geotechnical Society Special Publication, 2024)
In this study, the influence of the trajectory characteristics of horizontal bi-directional seismic motions on nonlinear seismic response and liquefaction was quantitatively evaluated using 1G shaking table tests. In order to evaluate the nonlinear response of liquefiable soils subject to bi-directional horizontal excitation, three types of bi-directional response spectrum-compatible ground motions with acceleration trajectories were used as inputs in the 1G shaking table test. The excitation acceleration in the shaking table test was based on the amplitude-adjusted wave of the NS component of the observed wave on the ground at the JMA Kobe in the 1995 Southern Hyogo Prefecture Earthquake, i.e., Level 2 earthquake ground motion for Type I ground (denoted by II-I-1) as shown in the specifications for highway bridges and its response spectrum. The accelerations are a kind of uni-directional input used in the current seismic design and seismic performance assessment, and two kinds of bi-directional accelerograms. The Uni-directional seismic wave is the linear trajectory with II-I-1. One of the two types of bi-directional seismic accelerograms is a circular trajectory, spectrum-compatible bi-directional accelerogram, which consists of a spectrum-matched unidirectional accelerogram and its Hilbert transform. The other type of bi-directional seismic acceleration is a bi-axial response spectrum-compatible with amplitude adjustment of the seismic ground motions observed at JMA Kobe in the 1995 Southern Hyogo Prefecture Earthquake. The bi-axial response spectra of these three acceleration trajectories are approximately identical. The 1G shaking table tests on liquefied soils were conducted at the Disaster Prevention Research Institute, Kyoto University, JAPAN. Liquefiable soils as a specimen were made of silica sand number 5, and the sand was prepared in a circular rigid steel container; response seismic acceleration and pore water pressure were measured in the saturated sand. By comparing the results of 1G shaking table tests of uni-directional and bi-directional excitations, the effect of bidirectional excitation on the nonlinear seismic response of liquefied soils was evaluated. As a result of the shaking table test, it is shown that the maximum response acceleration in the shallow part of the saturated sand is greater for bi-directional excitations than for uni-directional excitation. The maximum value of excess pore water pressure ratio was greater for bidirectional excitation than for uni-directional excitation. These results indicate that liquefaction is affected by bi-directional horizontal excitation. These results suggest the need to consider the influence of bi-directional horizontal excitation in seismic design and evaluation of seismic performance.